CFTR‐dependent chloride efflux in cystic fibrosis mononuclear cells is increased by ivacaftor therapy. Issue 7 (26th April 2017) - Guerra, Lorenzo; D'Oria, Susanna; Favia, Maria; Castellani, Stefano; Santostasi, Teresa; Polizzi, Angela M.; Mariggiò, Maria A.; Gallo, Crescenzio; Casavola, Valeria; Montemurro, Pasqualina; Leonetti, Giuseppina; Manca, Antonio; et al.
Abstract: Aim: The Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) potentiator ivacaftor (Kalydeco®) improves clinical outcome in G551D cystic fibrosis (CF) patients. Here, we have investigated whether ivacaftor has a clinical impact on non‐G551D gating mutations and function of circulating leukocytes as well. Methods: Seven patients were treated with ivacaftor and evaluated at baseline, and at 1‐3 and 6 months. Besides clinical and systemic inflammatory parameters, circulating mononuclear cells (MNC) were evaluated for CFTR‐dependent chloride efflux by spectrofluorimetry, neutrophils for oxidative burst by cytofluorimetry and HVCN1 mRNA expression by real time PCR. Results: Ivacaftor determined a significant decrease in sweat chloride concentrations at all time points during treatment. Body mass index (BMI), FEV1, and FVC showed an increasing trend. While C‐reactive protein decreased significantly at 2 months, the opposite behavior was noticed for circulating monocytes. CFTR activity in MNC was found to increase significantly at 3 and 6 months. Neutrophil oxidative burst peaked at 2 months and then decreased to baseline. HVCN1 mRNA expression was significantly higher than baseline at 1‐3 months and decreased after 6 months of treatment. The chloride efflux in MNC correlated positively with both FEV1 and FVC. On the other hand, sweat chloride correlated positively with CRP and WBC, and negatively with both respiratory function tests. A cluster analysis confirmed that sweat chloride, FEV1, FVC, BMI, and MNC chloride efflux behaved as a single entity over time. Discussion: In patients with non‐G551D mutations, ivacaftor improved both chloride transport in sweat ducts and chloride efflux in MNC, that is, functions directly imputed to CFTR.